(3GdQjGVjGJ GdEbJUGOjI (B:s (3GdeUahaGJ (B/s - (3TQGHj, YHO GdYRjRs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 1999)
(3eaghe GdeUahaI hHYV CfhGYgG(B- (3YedjGJ LHQjI Ydi GdeUahaGJ(B- (3GdeMOOGJ(B- (3ebdhH GdeUahaI(B- (3GTJbGb hJcGed GdeUahaGJ(B- (3GdEQJHGW hGdESJbdGd GdNWj ddeUahaGJ(B- (3QJHI GdeUahaI(B- (3LedI GdeYGOdGJ GdNWjI(B- (3LOGhd GdeONdGJ(B- (3GdeNQLGJ(B- (3JMdjd GdEfMOGQ(B.s
Keywords: (3GdEbJUGOs; (3GdQjGVjGJs